Integration Ecological and Economic Factors in Shaping Human Development: Evidence from ASEAN Countries - Madris, Madris; Manulusi, Muhammad Ridwan; Yunus, Amanus Khalifah Fil'ardy; Mubarak, Munawwarah S. (International Journal of Energy Economics and Policy, 2025)
In an era of unprecedented environmental challenges and socioeconomic disparities, evaluating human development by integrating ecological and economic dimensions has proven essential. This study examined the impact of environmental and economic factors on the Human Development Index in seven ASEAN countries using panel data collected from 1996 to 2022. We employed the Fully Modified Ordinary Least Squares (FMOLS) approach and confirmed the robustness of our results with Canonical Cointegrating Regression (CCR) and Dynamic Ordinary Least Squares (DOLS). Our findings revealed that an increase in ecological footprint per capita was associated with a reduction in the Human Development Index, whereas rises in gross domestic product, industrialization, foreign direct investment, and population density were found to enhance human development. These results highlighted the limitations of conventional measures of human development, which often ignore long-term ecological constraints. The study provided policy insights for designing balanced, sustainable, and equitable development strategies that harmonized economic growth with environmental protection. Future research should expand data coverage and apply advanced econometric techniques better to capture the complex interactions between economic and ecological factors. Policymakers can use these insights to inform strategies that promote both prosperity and environmental resilience.